(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Bridges are useful in society but also restrict water vehicles to pass through. Private vehicle owners are near the area, and the anchorage is only limited to the bay. The study of constructing a vertical-lift bridge will be undertaken at Manuel Roxas bridge in Binondo, Manila. The project will solve the aforementioned problem because it will allow water vehicles to pass through. This project aimed to determine the level of acceptability of a vertical-lift bridge in terms of construction materials, procedures and design, lifting mechanism, and presentation. The researchers used a quantitative-experimental design and utilized a purposive sampling technique to select 5 civil engineers and 20 5th-year Mechanical Engineering students of Bulacan State University as respondents. The researchers used statistical tools such as frequency and percentage, weighted mean, and t=test to answer specific problems. The following procedures were undertaken in making the model: get the proportions and measurements of the model; design the floor plan; prepare all the materials; construct the fixed section, lift span, tower of the bridge, column and footing, and the counterweights; set up the pulley mechanism; assemble the mechanism and counterweights; add additional details; undergo the operation of the model. The assessment of the vertical-lift bridge model was highly acceptable in terms of the aforementioned variables as assessed by civil engineers (3.50) and 5th-Year Mechanical Engineering students (3.50). This result indicated no significant difference between the assessments of the two groups of respondents on the level of acceptability of the model in terms of the aforementioned variables, with a variance of 0.13. Meanwhile, 5th-year Mechanical Engineering students obtained an overall weighted mean of 4.07, which was interpreted as highly acceptable with the variance of 0.56, a t-computed value of 1.64, and a degree of freedom 23 with the value of 2.50. The t-computed value was less than the t-critical value. Therefore, the overall assessment is highly acceptable. For further improvement of the proposed vertical-lift bridge, the respondents recommended focusing on the measurements and mechanism of the model. The two groups of respondents agreed that the model should conform to the standard design of bridges. The proponents should have managed their time wisely.